2017
DOI: 10.1161/atvbaha.116.308435
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein–Associated Apolipoprotein M Limits Endothelial Inflammation by Delivering Sphingosine-1-Phosphate to the Sphingosine-1-Phosphate Receptor 1

Abstract: Objective-Plasma high-density lipoproteins (HDL) are potent antiatherogenic and anti-inflammatory particles. However, HDL particles are highly heterogenic in composition, and different HDL-mediated functions can be ascribed to different subclasses of HDL. Only a small HDL population contains apolipoprotein M (ApoM), which is the main plasma carrier of the bioactive lipid mediator sphingosine-1-phosphate (S1P). Vascular inflammation is modulated by S1P, but both proand anti-inflammatory roles have been ascribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 51 publications
(82 reference statements)
4
105
0
3
Order By: Relevance
“…We considered the possibility that local levels of S1P were elevated by platelets and/or EC release during RAR and obscured the effects of ApoM deficiency. At higher levels of S1P (~500nM), albumin and ApoM have been shown to be equally effective at reducing TNF-α induced VCAM-1 in ECs in vitro [32]. …”
Section: Resultsmentioning
confidence: 99%
“…We considered the possibility that local levels of S1P were elevated by platelets and/or EC release during RAR and obscured the effects of ApoM deficiency. At higher levels of S1P (~500nM), albumin and ApoM have been shown to be equally effective at reducing TNF-α induced VCAM-1 in ECs in vitro [32]. …”
Section: Resultsmentioning
confidence: 99%
“…ApoM-bound S1P is a key component of HDL and is responsible for several HDL-associated protective functions (22). Many studies had shown that sphingosine-1-phosphate could attenuate organ injury and decrease the ability of the proinflammatory cytokine TNF-α to activate NF-κB (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Another study focused on the ApoM–S1P–S1PR1 signaling axis, which is proved to restrain the lymphocyte compartment and, subsequently, adaptive immune responses [25]. Specifically, in aortic primary endothelial cells, the anti-inflammatory effects of the ApoM-S1P complex are mediated by S1PR1 [26]. It is worth noting that patients with coronary artery disease have lower plasma S1P and HDL-S1P levels than controls [27].…”
Section: Discussionmentioning
confidence: 99%